The female body, confined and aggressed: Rethinking the other pandemic at home from a rereading of M. Merleau-Ponty and S. de Beauvoir - Avila Vera, Roger Park (2023)
The elaboration of this article stems from the interest in rethinking the conclusions of the study The other pandemic at home. In these we identified deficiencies in the prevention and immediate attention of the state system in the face of gender violence, which became even more evident during the SARS-CoV-2 pandemic in Peru. But, above all, we find a certain complicit silence that contributes to perpetuating cases of domestic violence against women in our country. To demonstrate this, we will start by explaining that the recognition of these deficiencies has an approach that stems from the exceptional circumstance of the pandemic and not from the structural problem of gender violence as such. Likewise, we will analyze confinement in terms of a new relationship of the human being with his around and the world in correspondence with the conceptual network of the body-world system of M. Merleau-Ponty. Finally, drawing on Simone de Beauvoir’s critique of the eternal feminine, we will interpret the forgetting of pre-confinement knowledge, coupled with the slightest suggestion that adequate preventive and corrective measures cannot be taken against gender-based violence, as an act of “bad faith”.